Influence of Levantine Artificial Reefs on the fish assemblage of the surrounding seabed - EDELIST, D.; SPANIER, E. (Mediterranean Marine Science, 2009)
Four Artificial Reef (AR) units were deployed at a 20m depth on a flat hard substrate 3 km west of Haifa, Israel and then surveyed for fish for 12 months. AR units supported 20 times the biomass of control quadrates and their enrichment impact was still significant at a radius of 13m away from units. The 13m values were also significantly higher than those of quadrates adjacent to units, suggesting the existence of a halo of relative depletion within the outer enrichment halo. The main species contributing to this pattern was the migrant herbivore Siganus rivulatus. A decrease in grazing resources is thus suggested as an explanation for creation of this halo. The most consistent AR residents were also Lessepsian migrants - Sargocentron rubrum, nocturnal predators which displayed high microhabitat fidelity and a steady increase in density. The 6 species of migrants recorded accounted for 65.3% of the commercially exploitable biomass and 25.2% of the specimens in the AR site. Other constant AR residents were the groupers Epinephelus costae and Epinephelus marginatus, which are rare and commercially important species. Site protection from fishing and storms were found to be of utmost importance, and design and deployment considerations are discussed.